Lupus community panel proposals for optimising clinical trials: 2018. Issue 1 (23rd March 2018) - Merrill, Joan T; Manzi, Susan; Aranow, Cynthia; Askenase, Anca; Bruce, Ian; Chakravarty, Eliza; Chong, Ben; Costenbader, Karen; Dall'Era, Maria; Ginzler, Ellen; Hanrahan, Leslie; Kalunian, Ken; et al.
Abstract : Formidable impediments stand in the way of treatment development for lupus. These include the unwieldy size of current trials, international competition for scarce patients, complex outcome measures and a poor understanding of these outcomes in the world at large. The heterogeneity of the disease itself coupled to superimposition of variegated background polypharmacy has created enough immunological noise to virtually ensure the failure of lupus treatment trials, leaving an understandable suspicion that at least some of the results in testing failed drugs over the years may not have been negative, but merely uninterpretable. The authors have consulted with many clinical trial investigators, biopharmaceutical developers and stakeholders from government and voluntary sectors. This paper examines the available evidence that supports workable trial designs and proposes approaches to improve the odds of completing interpretable treatment development programs for lupus.